Development of iSpring 9-Based Learning Media Using Android to Increase Learning Independence in Basic Pattern Dimensions - Panerus, Antika Cita; Irianti, Agus Hery Supadmi; Prahastuti, Endang (research, training and philanthropy institution Natural Aceh, 2024)
This research was developmental research that aimed to develop iSpring 9-based learning media using Android to increase student learning independence in basic fashion skills for Class X of SMK Negeri 2 Boyolangu, Tulungagung. The development method used the ADDIE model which includes: Analysis, Design, Development, Implementation and Evaluation. Validation was carried out by two expert validators: material experts and media experts. The data collection technique used a questionnaire. Validation results from material experts met the requirements of 85.00%, which means very valid, and the results from media experts met the requirements of 80.00%, which also means valid. A trial was conducted at the implementation stage. The results were that 34 students obtained an average score of 84.48% with very good qualifications, meaning this media is easy for students to learn. Therefore, it showed that the media is very suitable as a learning medium for pattern-making and helping students' teaching and learning process. A further developing learning media was suggested for the application to be developed and equipped with dimensions in basic fashion skills subjects following the school curriculum to sum the learning in one application.